The Limits of Online Price Discrimination in Europe - Sears, Alan M. (Science and Technology Law Review, 2021)
As big data capabilities have increased, so too has the potential for price discrimination. Price discrimination occurs when sellers offer goods and services at different prices to different consumers. Profiles of consumers can be created based on a variety of factors, such as their location, past purchases or behaviors online, or, more frequently, a large number offactors that, when combined, enables sellers to serve tailored prices based on differences between consumer profiles. In addition to these algorithmic forms of price discrimination, simpler methods are also in use, such as basing prices solely on the basis of a consumer’s IP address. This article aims to provide a comprehensive mapping of the boundaries of online price discrimination in Europe. While few legal provisions speak directly to online price discrimination or personalized pricing, a number of areas of law likely have a bearing on the extent to which price discrimination is legally permitted. As such, this article will examine competition law, consumer protection law, data protection law, and non-discrimination law in order to determine where online price discrimination may constitute noncompliance with one of the relevant provisions, as well as to denote where it appears that the framework is ill-equipped to adequately address the practice. Practical and sociological aspects relating to both online price discrimination and the application of the legal frameworks in these areas are also incorporated.